Zjawisko podpaleń w Polsce jako element ryzyka w działalności gospodarczej - Wieteska, Stanisław (Annales. Etyka w Życiu Gospodarczym, 2013)
The problem of fires in Poland is an important element of public safety. One of the reasons ofthe fires are different types of arson of buildings, crops or forests.This paper presents a quantitative scale of the phenomenon of arson in Poland. Basing on data from the General Headquarters of the Police and Fire Headquarters it analyzes the scale offire danger. It also presents the role of specialists in the detection of causes of fires. The article points the role ofinsurance in the compensation of fire damage.